The Health Literacy on Cannabis for Medical Use among Adult and Elderly People, Chiang Rai Province - Chairinkam, Wuthichai; Chomsri, Pimpisa; Matrakul, Mullika; Likhitsathian, Surinporn (Journal of The Royal Thai Army Nurses, 2022)
This research was a cross-sectional study. The objectives of this research are; to study the situation of health literacy on cannabis for medical use among adult and elderly in Chiang Rai province. Method: This research is a study of 463 people. A random sample selected by multi-stage sampling method, collected data by the questionnaire (Cronbach’s alpha coefficiency 0.95). The data were by descriptive statistics, Odds ratio (OR) and Independence t-test. Results: The participants were in adulthood (n = 359) and older adults (n =114). The majority of the adult participants had poor health literacy (68.4%). Most of the older adult participants had poor health literacy (86.8%). The adult participants had a moderately level to very good level of health literacy more than the older adult participants (OR= 3; 95% CI: 1.69-5.48). Most of the adult participants had low health literacy in communication skill and decision skill. Most of older adult participants had low health literacy in Access skill, knowledge skill, media literacy skill, communication skill and decision skill. Conclusion: Most of participants had a low level of health literacy about cannabis for medical use, especially the elderly group. Therefore, program of enhancing health literacy about cannabis for medical use program may be necessary, especially among the older adult.